COVID-19, school closures, and student learning outcomes. New global evidence from PISA - Maciej Jakubowski; Tomasz Gajderowicz; Harry Anthony Patrinos (npj Science of Learning)
Abstract The COVID-19 pandemic resulted in significant disruption in schooling worldwide. Global test score data is used to estimate learning losses by modeling the effect of school closures on achievement by predicting the deviation of the most recent results from a linear trend using data from all rounds of PISA. Mathematics scores declined an average of 14 percent of a standard deviation, roughly equal to seven months of learning. Losses are greater for students in schools that faced relatively longer closures, for boys, immigrants, and disadvantaged students. Educational losses may translate into significant national income losses over time.